The sociology of happiness in Buenos Aires - Scribano, Adrián Oscar (2016)
For some time in Argentina, and especially in Buenos Aires City, we have been conducting research on the structure of sensibilities. One of these experiences is based on the question of this paper: What does it mean to be happy for someone who lives in Buenos Aires? Are porteños, those who live in Buenos Aires, happy? This paper seeks to describe one of the most important components of contemporary politics of emotions: the state of happiness in Buenos Aires. To achieve this goal, we propose the following argumentative strategy: a) explaining briefly the importance that happiness studies have achieved; b) outlining some conceptual axes to understand the politics of emotions; c) presenting some results from two surveys of sensitivities conducted in 2010 and 2012 (selecting only the questions that relate to happiness); d) discussing and synthesizing these findings; and e) proposing some clues for an interpretation and an open closure. We argue that in order to understand the state of happiness, we should relate it to the consolidation of a normalized society based upon the immediate enjoyment, and/or as an interstitial practice. This proposed interpretation allows us to outline some questions to further research around the connections between happiness and emotions politics.